The role of strategic leadership in achieving the dimensions of competitive advantage in university libraries: a case study of the university library at the Faculty of letters and Humanities and Social Sciences at The University of Annaba - Bouchaour, Assia; Boumengar, Mourad (Journal of Human Sciences, 2023)
The objective of the study is to identify the role of strategic leadership in all its commutative, transformative and entrepreneurial variants in the realization of competitiveness at the Faculty of letters, humanities and Social Sciences library in Annaba University. The study relied on the descriptive analytical approach, and the questionnaire was designed for this purpose after having been presented to the jurors for its truthfulness and stability, it was distributed to 26 librarians using the comprehensive inventory approach. The study revealed a series of findings, the most important of which are: The dominant leadership model in the library in question is the transformative leadership model. The study also showed that the dominant leadership model plays a positive and effective role in achieving certain aspects of competitiveness, such as cost reduction and hyper-responsiveness, and, in light of the results achieved, the study made recommendations that serve its objectives.